Método para análise do fluxo logístico fundamentado no mapeamento do processo e na gestão de indicadores estratégicos: uma proposta para o setor calçadista - Martins, Jarbas Rocha (2014)
The domestic footwear industry has faced the challenge of an inevitable globalization that leads to unfair competition with Asian countries. This scenario suggests as an effective tool, the integration between the companies for their strengthening and thus respond to this globalization by increasing their competitiveness through the efficient use of technological innovations that have driven the industry globally, as technology information applied to the management of logistics flow. However, beyond the essential associations, companies need to review their traditional organizational culture and align its strategic vision for the scenario described above, and disseminate, make that vision satisfactorily reach the productive sector, affecting mostly those who matter: the consumers. Thus, this paper proposes a method of analyzing the efficiency of logistics flow in a company in the footwear business, based on the process mapping and the development of a management model of strategic indicators, presenting a methodology that will assist in the evaluation of its operations logistics, mapping its logistics flow and aiding in the decision to make the supply chain more efficient and flexible. Thus contributing to the absorption capacity of the technological opportunities of integrating parts of the chain, such as information technology. The study is done by mapping the logistics flow and managing the use of strategic performance indicators, a company focused on the footwear branch belonging to the local productive arrangement (APL) in Ceará cariri which, in turn, stands out as a major footwear producers poles on the national scene.